Indonesia’s capital city relocation: A perspective of regional planning - Farida Farida (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
The role of a capital city is essential for a nation. Indonesia’s plan to relocate its capital from Jakarta to North Penajam Paser has been set in stone. The Indonesian government targets the relocation to be executed in 2024; therefore, the preparations and capital city development must start from 2020. This research aims to study capital relocation from the perspective of regional planning concerning institutional, spatial planning, the economy, social aspects, and the environment. The data source used in this research was the secondary data obtained from literature review and document analysis. The new capital must present a distinct identity, as it will determine the institutional that will lead to success. The main reasons for the capital relocation are growth and economic equality for the eastern part of Indonesia. It means that development will be encouraged to achieve these goals. On the other hand, overly rapid development in the new capital is also undesirable—a challenging paradox for the institutions involved that demands creativity and innovation for a successful capital relocation.